2021
DOI: 10.1002/arch.21835
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a catalase gene from the green peach aphid (Myzus persicae)

Abstract: The green peach aphid, Myzus persicae (Sulzer), is a serious agricultural pest with a worldwide distribution. Catalase (CAT), which is encoded by the catalase (Cat) gene, is an extremely important antioxidant enzyme that plays a pivotal role in protecting cells against the toxic effects of hydrogen peroxide. The Cat gene has not been characterized in M. persicae; therefore, this study describes the identification of the Cat (MpCat) gene from M. persicae. MpCat contains an open reading frame of 1515 bp and enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(81 reference statements)
1
4
0
1
Order By: Relevance
“…When B. tabaci adults were subjected to CAT silencing and a high temperature, their ROS levels gradually returned to the normal level after recovery for 24 h at 25 °C, this indicated a negative regulation interaction between ROS level and CAT expression level. Previous studies with insects also showed that the CAT genes might be involved in the high temperature tolerance but only by whether this gene's transcription level was significantly induced by high temperature or not (Lu et al, 2017;Xu et al, 2017;Cheng et al, 2018;Li et al, 2018;Li et al, 2021). Here, our findings with B. tabaci provide direct evidence that CAT genes contribute to heat tolerance by eliminating excessive ROS (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…When B. tabaci adults were subjected to CAT silencing and a high temperature, their ROS levels gradually returned to the normal level after recovery for 24 h at 25 °C, this indicated a negative regulation interaction between ROS level and CAT expression level. Previous studies with insects also showed that the CAT genes might be involved in the high temperature tolerance but only by whether this gene's transcription level was significantly induced by high temperature or not (Lu et al, 2017;Xu et al, 2017;Cheng et al, 2018;Li et al, 2018;Li et al, 2021). Here, our findings with B. tabaci provide direct evidence that CAT genes contribute to heat tolerance by eliminating excessive ROS (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…, 2018; Li et al. , 2021). Here, our findings with B. tabaci provide direct evidence that CAT genes contribute to heat tolerance by eliminating excessive ROS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CAT was also reported to play important roles in the thermal tolerance of insects. Suppressing CAT significantly reduced the survival rate of Myzus persicae under heat stress ( Li et al, 2021 ). In the whitefly Bemisia tabaci , CAT help to adapt to high temperature by scavenging excessive ROS ( Liang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cat, expressed by the peroxidase gene, is a key antioxidant enzyme in the body, primarily responsible for the breakdown of toxic H 2 O 2 . 49 Obesity raises H 2 O 2 levels significantly owing to lower Cat expression, increasing oxidative stress in the body and causing cardiovascular disease. 50 , 51 However, oxidative stress caused by Cat deficiency may alleviate obesity-related metabolic problems by decreasing inflammation.…”
Section: Discussionmentioning
confidence: 99%